The coalescent - Beerli, Peter (Henry Stewart Talks, 2022)
Coalescent theory, Wright-Fisher population model, The probability of having an ancestor in the population model, Coalescence of two lineages, Probability calculation on genealogy, Coalescence of a large number of samples, Variability of the coalescent process, Infer population size from data, Mutation-scaled population size, Estimating population size using Bayesian inference